Indonesian smart schools: Their influence on the ability of information literacy on the biology field - Adhitya Amarulloh; Endang Surahman; Vita Meylani (JURNAL BIOEDUKATIKA, 2020)
Information literacy in the information society era is very important for every individual, especially for students to prevent misunderstandings and misconceptions. Digital-based learning can influence on students' information literacy abilities. The purpose of the study is to look at the effect of digital-based learning (Indonesian Smart Schools) on students' information literacy abilities. This research was conducted from February to June 2019, at SMA Negeri 2 Tasikmalaya. The research method was a true-experimental design with randomized pretest-posttest control group design. This study population was class X, amounting to 299 people, with cluster random sampling technique, the results were class X MIPA 1 (experimental) and X MIPA 5 (control). The information literacy research instrument uses a validated instrument from SAILS (30 items). Based on the ANCOVA analysis at the significance level (Î) = 0.05 and based on the comparison of the values gain, it can be concluded that there was an effect of digital-based learning on students' information literacy abilities on Animalia material. Indonesian Smart Schools can be alternative digital learning to hone the ability of information literacy on Animalia material. Indonesian Smart Schools can be an alternative to digital learning to hone the ability of information literacy.